Effect of Wire Diameter, Feeding Rate, Pulse (on/off) Time on Surface Roughness and Metal Removal Rate for Cr-Mo Steel (SCM425H) During Wire Electrical Discharge Machine (WEDM) Cutting Operation - Saad Shather; Sami Hammood; Noor Al-Huda Hussain; Noor Hasson (Engineering and Technology Journal, 2020)
Increase the demand to produce complex shapes with high quality and dimensional accuracy such as production aerospace, cars, die sinking has been leading to increase the demand to use the non- traditional cutting operations such as wire electro-discharge machine (WEDM) rather than using the traditional operations. An idea to understand the effect of wire diameter, wire feed, pulsing (on/off) time on surface roughness, and metal removal rate of Cr-Mo steel during wire electrical discharge machining was investigated. Two Steel alloy samples with dimensions of (60 x50 x 20)mm were cut into four rectangular spaces with (5x10x20)mm at one side of each sample using wire cut (EDM) machine with a wire diameter of 0.25 mm and feeding rate 2 m/min for sample 1 and a 0.3 mm diameter and 3 m/min feeding rate for sample 2. Pulse (on, off) time was (110, 50), (112, 52), (115, 55), (116, 57) corresponds to space 1, space 2, space 3, and space 4 in both steel block. Surface roughness and metal removal rate measurements were estimated. The results showed that wire diameter, feeding rate, and pulse (on, off) time is proportional with metal removal rate, while reversed with surface roughness. The wire diameter of 0.3 mm and a feeding rate of 3m/min enhanced better surface quality and productivity. Pulse (on, off) time is the most effective parameter. Best duration time was recorded at the values (116, 57)